Leveraging International Large-Scale Assessments: Insights from an Item-Writing Professional Development Program for High School Mathematics Teachers - Garcia, Mark Lester B. (Archīum Ateneo, 2024)
The Philippine Department of Education, despite seeing minimal improvements in the country’s score and rankings in the recent cycles of international large-scale assessments (ILSAs) such as TIMSS and PISA, maintained that it shall continue to participate in ILSAs to monitor the progress of educational effectiveness and benchmark with other countries by observing and adopting commendable practices. While legislators and other stakeholders push for increased financial resources in the education sector as part of the country’s preparations for upcoming ILSAs, one crucial aspect that is largely overlooked is teacher training. This paper presents a viable yet contentious way of upskilling teachers – one that leverages ILSAs by training teachers to write or construct prototype items inspired by those in ILSAs. In this study, nine high school mathematics teachers participated in an item-writing seminar-workshop on constructing PISA-like items. As part of their in-service training, they were required to produce eight items each as individual outputs, which were then reviewed by external experts for feedback. Results from the experts’ qualitative and quantitative feedback showed that the teachers mostly produced satisfactory items that comply with the constraints posed by the PISA mathematics assessment framework, despite their initial difficulties in understanding it and its cognitive categories.